(untitled) (The Research of Medical Science Review, 2024)
Background: Nurses are the largest group of healthcare providers. Health programs effects most nurses and midwives who play a significant part in the growth of the profession and are able of rehearsing in different surrounds. Pakistan is a less developing country; nurses are not so developed there is very limited such organization that in which nurses make polices. Nurses are most of the time busy in burden of patient they are mostly working at the bed side so there is extreme need of policy development and in Pakistan, the level of engagement of nurses in health policy is not well understood, and the perceived advantages and disadvantages of nurses in policy-making processes are also unknown.Aims: To find out the level of involvement of nurses in health policy development in tertiary health care setting. Material & Method: A descriptive cross sectional study was carried out among nurses in tertiary health care setting Peshawar. Data were collected from 327 nurses through questionnaires. Convenient sampling technique was used for participant’s selection. Written informed consent was taken from all participants.Results; There were 327 participants in this study, including 51.1% female and 48.9% male, 79.2% under 30 and 20.8% over 30, and educational backgrounds (41% BSN, 29.1% post-RN, 29.6% diploma in general nursing, and 0.3% MSCN). The ranges of nursing experience among the participants were 0–5 years (53.2%), 6–9 years (19%), and more than 10 years (27.8%). Out of the 327 participants only 108 (33.0%) participated in health policy making or they ware being a part of policy team while the other 77% did not participated in health policy development. Conclusion: Nurses play a important role in shaping health policy. This project found a low level of involvement among nurses in health policy formation, despite their crucial role. These findings serve as a baseline for nurse leaders and administrators seeking to improve nurses' participation in health policy. Nurses' participation in health policy activities may be increased by emphasizing the benefits of health policy participation, as well as health policy education and training.